Pengaruh Keragaman jenis inang terhadap diameter dan tinggi batang anakan cendana (Santalum album L.) - MOI MEO, MONIKA (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2024)
Sandalwood (Santalum album L.) is an endemic plant and an important natural resource in improving the economy of East Nusa Tenggara (NTT). Sandalwood has a very fragrant aroma and contains essential oils so that it has a high selling value and is one of the sources of regional income (PAD). Sandalwood growth is very slow in nature due to its parasitic nature. To meet its nutritional needs, it depends on the host plant so that sandalwood needs to establish an association with other plants (hosts) in order to survive through haustoria formed from sandalwood plant roots. This study aims to determine the diameter and height of sandalwood seedlings planted with a combination of several types of hosts. The study was conducted in TDM 2 Village, Kupang NTT, using an experimental method with a completely randomized design (CRD) consisting of 4 treatments and 5 replications. The results of statistical analysis showed that the diversity of host types had a significant effect on the increase in the height of sandalwood seedlings and had a very significant effect on the diameter of sandalwood seedlings, this is evidenced by the sandalwood stem height analysis table. The highest average height of sandalwood seedlings was found in treatment P2 with an average height of 84.3 and the highest average diameter of sandalwood seedlings was found in treatment P1, namely 3.85.